Выход на бис: роман / Леонид Влодавец - Влодавец Леонид Игоревич (Черная кошка, 1997)
Экземпляры: аб. (2005) / Инвентарный номер: 48939 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 58 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44